The Impact of National Culture on the Success of construction Projects - AbuZaher, Said Ahmed (2015)
The objective of the study is to examine how national cultural differences impact upon the successful delivery of construction projects in United Arab Emiretaes (UAE). The research did a literature review to understand different viewpoints and created a framework which framed that cultural dimensions influence people’s attitudes, values, practices, and behaviours The conceptualization and flexibility with which Hofstede’s cultural model has been developed makes it a suitable framework to adopt in project management research involving cross-cultural aspects. As such, it adoption in the current study will help guide the identification of the gaps of the study. The research did a quantitative analysis where the survey was used to gather data. Around150 people responded with their answers. The finding was done for 6 stages of the project management at the stage of planning, reaching major milestone, completion of project, handover stage, handling of project and decommissioning of project. These 6 stages and the perception of each stage about the success and failure of the project were done and this brought some new insights of the research. The survey analysis reflected that these factors are very crucial to the success and failure of the project: Achievement of intended outcomes as defined by clients/owner/sponsor, planned and approved project scope, planned and approved project time, planned and approved project budget, the project team etc.